3D thermal modelling of the Oslo-Asker area, Norway. (July 2022) - Pascal, Christophe
Highlights: Recent research point to relatively high heat in the Oslo Metropolitan Area, Norway. Subsurface temperatures are computed for the Oslo-Asker area by means of 3D numerical modelling. Temperatures modelled for shallow depths (i.e. < 500 m depth) appear to be of economic interest. Modelled deep temperatures are merely not of economic use with the present-day technology at hand. Abstract: The pressing need for renewables prompted geothermal research in Norway recently. These studies confirmed rocks with high heat-generation rates in the Oslo Region, covered locally by sediments. Although the geology appeared favourable to the operation of deep geothermal resources in the most densely populated area of Norway, no attempt was made to estimate underground temperatures. In the present work, subsurface temperatures were computed for the Oslo-Asker area by means of 3D numerical modelling. We conclude that deep temperatures are too low to be of economic use with present-day technology. Shallow temperatures (i.e. < 500 m depth below ground level) appear high enough for direct use and heating. There is, however, a crucial need for new data from deep boreholes in order to better constrain the predictions of the models.